Integration of Curricula (Curriculum 2013 and Cambridge Curriculum for Junior High School Level in Three Subjects) in Pandemic Situation - Marudut Bernadtua Simanjuntak; Muchlas Suseno; Samsi Setiadi; Ninuk Lustyantie; Irma Rasita Gloria Rasita Gloria Barus (Ideas Publishing, 2022)
This study aims to determine and set the effective integration of the Cambridge Curriculum as an adaptive or supporting curriculum to the National Curriculum (K13) during the pandemic. The object is simplified into three junior high school subjects: mathematics, science, and English. This study applies a qualitative method by comparing and adopting the syllabus indicators of three subjects into the National Curriculum (K13) and adapted to online learning. The result shows that integration suitability is compared and matched between the two curricula and is ready to be applied during the pandemic. The expected implication is that the Cambridge Curriculum can help schools around the world improve the quality of learning, especially during the pandemic. Penelitian ini bertujuan untuk mengetahui dan menetapkan efektifitas integrasi kurikulum Cambridge sebagai kurikulum adaptif atau penunjang terhadap Kurikulum Nasional (K13) di masa pandemi. Objek tersebut disederhanakan menjadi tiga mata pelajaran SMP: matematika, IPA, dan bahasa Inggris. Penelitian ini menggunakan metode kualitatif dengan membandingkan dan mengadopsi indikator silabus tiga mata pelajaran ke dalam kurikulum nasional (K13) dan disesuaikan dengan pembelajaran online. Hasil penelitian menunjukkan bahwa kesesuaian integrasi dibandingkan dan dicocokkan antara kedua kurikulum dan siap diterapkan pada masa pandemi. Implikasi yang diharapkan adalah kurikulum Cambridge dapat membantu sekolah-sekolah di seluruh dunia meningkatkan kualitas pembelajaran, terutama di masa pandemi.